(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
This article covers the development of a student career recommendation system, an educational innovation that assists students in planning career options or professional skills based on graduate profiles. Choosing a student’s career path in higher education without the proper service information in the career recommendation route can lead to challenges in suggesting a profession by students based on their field of expertise and profiles of graduates of the study program they are interested in. In higher education, choosing a student’s career path without the right service information in the career recommendation path can cause difficulties in recommending a career by students according to the field of expertise and profiles graduates of the study program they are interested in. This study aims to develop a student career path recommendation system using an expert system through an innovative Career Path Recommendation Expert System (CPRES) system that is already valid and its practicality is proven by the usability score approach, while the effectiveness of the student career model uses an expert system (CPRES) analyzed based on the level of rigor.